Inventing aliens: immigration control, 'xenophobia' and racism in Japan. (January 2017) - Park, Sara
This paper, which examines a growing problem of popular racism in Japan against ethnic minorities, especially Koreans, is critical of the way in which it is often being passed off as xenophobia. The author argues that to confront the current racism means coming to terms with Japan's colonial past and also the immigration control system which labels all ethnic minorities, including those born in Japan during and following imperial conquest, as 'foreign'. Since 2009, ultra-right groups, especially the Zaitokukai, have spread popular racism on the internet and attacked people on the streets. In 2013, they began demonstrations in major cities. Activists, politicians and academics, who are worried about the growing racism, have launched counter movements and demanded that new legislation regarding hate speech should be passed. However, because of the way the problem is generally being framed in relation to the rights and status of foreigners in Japan, the authorities underestimate the seriousness of the situation and its historical genesis. Continuing to use the term xenophobia trivialises the issue, suggesting it only relates to minority groups temporarily resident in Japan.